Design as Bootstrapping. On the Evolution of ICT Networks in Health Care - Hanseth, O.; Aanestad, M. (Methods of Information in Medicine, 2003)
Objectives: This paper assumes that in addressing major challenges related to telemedicine as networks enabling huge improvements of heath services we need to move beyond complexity and rather focus on the very nature of such networks.Methods: The results of this paper are based on an interpretive analysis of three case studies involving telemedicine, i.e. broadband networks in minimal invasive surgery, EDI infrastructures and telemedicine in ambulances.Results and Conclusion: The well-known concept of “critical mass” focuses on the number of users as a significant factor of network growth. We argue however, that we should not only consider the size of the network, but also the heterogeneity of its elements. In order to discuss heterogeneity along several dimensions, we find Granovetter’s and Schelling’s models of diversity in individual preferences helpful. In addition to the heterogeneity of the individual users, we discuss heterogeneity related to use areas and situation, to technologies, etc. The interdependencies and possible conflicts between these dimensions are discussed, and we suggest “bootstrapping” as a concept to guide the navigation/exploitation in/of these dimensions.
Keywords: Network growth; critical mass; bootstrapping; telemedicine